Histiocytoid Sweet syndrome: Report of two cases and review of the literature - Ching-Fu Huang; Bai-Yao Wu; Fang-Yih Liaw; Wei-Ming Wang; Chien-Ping Chiang (Wolters Kluwer Medknow Publications, 2012)
Histiocytoid Sweet syndrome (SS) is a rare inflammatory disease that has recently been described as a variant of classic SS. Histopathologically, histiocytoid SS is characterized by papillary dermal edema with infiltration of histiocyte-like cells into the upper dermis. These microscopic features may be similar to those of leukemia cutis, which involves infiltration of malignant blasts into the dermis. However, the treatment and clinical prognosis of these two conditions are quite different. Here, we report the case of two Taiwanese patients with histiocytoid SS. Interestingly, one of the patients had a history of myelodysplastic syndrome and was initially considered to have ongoing leukemic transformation with concomitant leukemia cutis. Finally, the patient was diagnosed with histiocytoid SS based on histological findings, and both patients were successfully treated with low-dose oral corticosteroids.